Acoustic emission response and micro-deformation behavior for compressive buckling failure of multi-delaminated composites. (August 2016) - Zhou, Wei; Lv, Zhi-hui; Li, Zhi-yuan; Song, Xiang
Accurate characterization of delamination damage and evolution plays a significant role in studying the failure behaviors of composite laminates. In the present research, both acoustic emission and digital image correlation technology are used to simultaneously monitor the buckling process of multi-delaminated composites under compression. Three kinds of composite specimens are carried out to investigate the influence of delamination lengths and positions on the compressive behaviors of the composites. Meanwhile, the buckling load, micro-displacement fields of interfacial zone and acoustic emission response characterizations are also obtained. The results indicate that acoustic emission parameters such as hits, amplitude, duration and relative energy are correlated with the damage process of composite specimens, while the critical damage deformation of delamination regions is clearly exhibited from digital image correlation results. Furthermore, the buckling behaviors are significantly influenced by the thickness of sub-layer and the lengths and positions of delaminations. The complementary nondestructive testing technologies combining acoustic emission with digital image correlation are beneficial for in situ damage monitoring of the composites.